The influence of Tetranychus cinnabarinus-induced plant defense responses on Aphis gossypii development - Guang-min MA; Xue-yan SHI; Zhi-jiao KANG; Xi-wu GAO (Journal of Integrative Agriculture, 2018)
Carmine spider mites (Tetranychus cinnabarinus) and cotton aphids (Aphis gossypii) are both serious pests of cotton, and cause reductions in yields of this key agricultural crop. In order to gain insights into how plant defense responses induced by one herbivore species affect the behavior and performance of another, we examined how infestation with T. cinnabarinus influences the development of A. gossypii using cotton as a model. In this study, we measured the activities of several important biochemical markers and secondary metabolites in the leaves of cotton seedlings responding to infestation by T. cinnabarinus. Furthermore, the influences of T. cinnabarinus infestation on the development of A. gossypii in cotton were also examined. Our data showed that the activities of several key defense enzymes, including phenylalanine ammonia-lyase (PAL), peroxidase (POD), lipoxygenase (LOX), and polyphenol oxidase (PPO), were substantially increased in cotton seedlings responding to spider mite infestation. Further, the contents of gossypol and condensed tannins, key defensive compounds, were significantly enhanced in leaves of cotton seedlings following T. cinnabarinus infestation. Moreover, the T. cinnabarinus-induced production of defense enzymes and secondary metabolites was correlated with infestation density. The developmental periods of A. gossypii on cotton seedling leaves infested with T. cinnabarinus at densities of 10 and 15 individuals cm−2 were 1.16 and 1.18 times that of control, respectively. Meanwhile, the mean relative growth rates of A. gossypii on cotton leaves infested with T. cinnabarinus at densities of 8, 10 and 15 individuals cm−2 were significantly reduced. Therefore, these data suggested that the developmental periods of A. gossypii were significantly lengthened and the mean relative growth rates were markedly reduced when cotton aphids were reared on plants infested with high densities of spider mites. This research sheds light on the role that inducible defense responses played in plant-mediated interspecific interactions between T. cinnabarinus and A. gossypii.